Pseudotyped Vesicular Stomatitis Virus-Severe Acute Respiratory Syndrome-Coronavirus-2 Spike for the Study of Variants, Vaccines, and Therapeutics Against Coronavirus Disease 2019 - Salazar-García, Marcela; Acosta-Contreras, Samyr; Rodríguez-Martínez, Griselda; Cruz-Rangel, Armando; Flores-Alanis, Alejandro; Patiño-López, Genaro; Luna-Pineda, Victor M. (Frontiers in Microbiology, 2022)
World Health Organization (WHO) has prioritized the infectious emerging diseases such as COVID-19 in terms of research and development of effective tests, vaccines, antivirals, and other treatments. SARS-CoV-2, the etiological causative agent of COVID-19, is a virus belonging to risk group 3 that requires Biosafety Level (BSL)-3 laboratories and the corresponding facilities for handling. An alternative to these BSL-3/-4 laboratories is to use a pseudotyped virus that can be handled in a BSL-2 laboratory for study purposes. Recombinant Vesicular Stomatitis Virus (VSV) can be generated with complementary DNA from complete negative-stranded genomic RNA, with deleted G glycoprotein and, instead, incorporation of other fusion protein, like SARS-CoV-2 Spike (S protein). Accordingly, it is called pseudotyped VSV-SARS-CoV-2 S. In this review, we have described the generation of pseudotyped VSV with a focus on the optimization and application of pseudotyped VSV-SARS-CoV-2 S. The application of this pseudovirus has been addressed by its use in neutralizing antibody assays in order to evaluate a new vaccine, emergent SARS-CoV-2 variants (delta and omicron), and approved vaccine efficacy against variants of concern as well as in viral fusion-focused treatment analysis that can be performed under BSL-2 conditions.